PENGARUH PRAKTIKUM BERWAWASAN LINGKUNGAN DENGAN MODEL INKUIRI TERHADAP SIKAP ILMIAH DAN HASIL BELAJAR - Maesarah, Siti; Nufida, Baiq Asma (Hydrogen: Jurnal Kependidikan Kimia, 2019)
This study aims to determine the effect of the experiment based environmental on scientific attitude of the student and learning achievement on acidand alkali subject. This study was quasi-experimental with Posttest-Only Control Group Design. The sample consists of two intact group, experimental group (learning by experiment based environmental method) and control group (learning by traditional method) choosen by purposive sampling technic. Data collection of scientific attitude using questionnaires and observation sheets, while learning outcomes data collected by an objective test. Data analyzed with descriptive statistic and non parametric statistic (Mann Whitney test). The result show that student’s scientific attitude score of experiment group is 83.35 at very high category while the control group is 77.82 at the high category. The average score of learning achievement 86.40 for experimental group higher than control groupis 70.87. Beside that Mann-Whitney test obtained sig. less than 0.05 (p <0.005). Thus, it can be concluded that the experiment based environmental methods affect the scientific attitude and student learning achievement on acid-base subject.